Modeling and Analysis of New Multilevel Inverter for Solar Photovoltaic Power Plant - Xiaoqiang Guo; Ran He; Mehdi Narimani (International Journal of Photoenergy)
Solar photovoltaic (PV) power plant is an effective way to utilize the renewable energy sources. EMI is one of the major concerns in PV power plant. Typically, the multilevel inverters are used in high voltage PV power plant. However, the conventional multilevel inverters require more semiconductors, which complicate the circuit structure and control algorithm. In this paper, a novel five-level inverter is introduced for the high voltage PV power plant applications. The model of the inverter is analyzed. With the redundant switching states, a new modulation strategy is proposed to reduce the common-mode voltage and EMI. The proposed approach is able to eliminate the common-mode voltage; meanwhile it has the capability of balancing the capacitor voltages. The cosimulation tests with the Matlab/Simulink and S-function are carried out. The results verify the effectiveness of the proposed method.